Adenoid basal cell carcinoma: An underrecognized cervical malignancy - Arielle Katcher; Juliana Schilsky; Alisha Daroch; Tahyna Hernandez; Andrew Menzin; Lisa Dos Santos; Jill Whyte; Marina Frimer (Gynecologic Oncology Reports)
Introduction: Adenoid basal cell carcinoma is a rare cervical malignancy which is indolent in nature but resembles more commonly occurring aggressive malignancies. Cases: Here we describe three cases of cervical adenoid basal cell carcinoma. All patients had a history of cervical dysplasia with high-risk HPV. The first and second patient were treated with hysterectomy, and the third patient opted for surveillance after cold knife conization. All patients have no evidence of disease to date. Conclusion: Cervical adenoid basal cell carcinoma is a rare malignancy that requires careful diagnostic attention due to its histologic similarities to more aggressive malignancies and the risk of misclassification. Advances in diagnostic criteria including immunohistochemistry (IHC) classification are key to distinguishing this unique pathological entity. Definitive treatment depends on accurate diagnosis. Optimal treatment involves surgical management with hysterectomy and lymph node assessment. Excisional biopsy with thorough pathologic evaluation for invasive carcinoma can be considered in patients who desire future fertility.